Pandemic legalities : legal responses to COVID-19 : justice and social responsibility / edited by Dave Cowan and Ann Mumford. - Cowan, David (David S.); Mumford, Ann (Law, society, policy series., 2021)
The effects of COVID-19 are visited disproportionately on the already disadvantaged. This important text maps out ways in which those already disadvantaged have been affected by legal responses to COVID-19. Contributors tackle issues including virtual trials, adult social care, racism, tax and spending, education and more. They reflect on the implications of COVID-19 and express concerns with policy and practice developments and with the neutral version of the law and the economy which has taken root. Drawing on diverse resources, this text offers an account of the damage caused by legal responses to the pandemic and demonstrates how the future response can be positive and productive.